Biobriket Berbasis Limbah Lignoselulosa Berstandar Mutu SNI: Review - Mochammad Fajar Aliyyansyah; Cantika Wahyu Maharani; Reni Febriani; Asep Kadarroman (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2025)
The depletion of non-renewable energy reserves encourages the development of alternative renewable energy sources, such as biomass energy. Biomass is an organic material derived from living organisms and contains biochemical compounds such as carbohydrates, proteins, and fats. Moreover, biomass also contains lignocellulose, which holds significant potential as a raw material for energy products such as bio briquettes. This article aims to examine the characteristics of bio briquettes from lignocellulose waste based on SNI briquette quality standards. Data search using literature studies with searches on Google Scholar, Research Gate, and ScienceDirect with the keywords